Artificial Synapses: Gate‐Tunable Synaptic Plasticity through Controlled Polarity of Charge Trapping in Fullerene Composites (Adv. Funct. Mater. 50/2018). (10th December 2018) - Ren, Yi; Yang, Jia‐Qin; Zhou, Li; Mao, Jing‐Yu; Zhang, Shi‐Rui; Zhou, Ye; Han, Su‐Ting
Abstract : In article number1805599, Ye Zhou, Su‐Ting Han and co‐workers demonstrate a flexible organic synaptic transistor capable of concurrently exhibiting signal transmission and learning functions. Fullerene trapping sites are doped in polymer by facile solution process to form the hybrid active structure. Comprehensive synaptic functions have been successfully emulated in this three‐terminal device.